The effect of trust and income on motivation to pay zakat - Laili Irawati; Fernaldi Anggadha Ratno (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
This study aims to determine the effect of trust and income on the motivation to pay zakat. This type of research is quantitative research. The data collection technique was carried out by distributing questionnaires distributed to Muzakki Griya Zakat Suruh Semarang district. The samples taken for the study were 67 respondents using probability sampling techniques. The analysis used is using multiple linear regression. The test results show that the variables of trust and income positively affect the motivation to pay zakat. The variables of trust and income together influence the motivation to pay zakat.